The Role of Magnetic Skeleton in Solar Flare Filaments Activity - Guo, Juan; Wang, Huaning; Wang, Jingxiu; Zhu, Xiaoshuai; Huang, Jing; Chen, Shanqiang; Luo, Bingxian; Liu, Siqing; Deng, Yuanyong; Lin, Jiaben (The Astrophysical journal, 2024)
We report an M9.3 flare and filaments activities from NOAA Active Region 11261 that are strongly modulated by the 3D magnetic skeleton. Magnetic field extrapolation from the vector magnetic field suggests complex magnetic connectivity and the existence of a high coronal null point southeast of the active region. A small filament over the inversed V-shaped polarity inversion line erupted and resulted in the M9.3 flare associated with a weak ejection in the EUV hot channel and the formation of a relatively large filament. Both the weak ejection and the eruption of the large filament were toward the southeast. Comparative analyses have disclosed the following new facts. First, the trajectory of looptop hard X-ray emission provides solid evidence that the magnetic reconnection site propagated up toward the coronal null point as the flare and filaments erupted. Second, the EVU observations show coronal mass ejection-like eruption features in the ejection region of the magnetic skeleton. Third, the closed fan confined the west end of the large filament and the corresponding flare ribbons. We demonstrate a spatiotemporal relationship between the magnetic skeleton and the flare filament activity. We conclude that the magnetic skeleton can modulate and determine almost all the characteristics of the studied activity in the corresponding scale.